DOTA Conjugate of Bisphosphonate and PSMA-Inhibitor: A Promising Combination for Therapy of Prostate Cancer Related Bone Metastases - Grus, Tilmann; Lahnif, Hanane; Bausbacher, Nicole; Miederer, Matthias; Rösch, Frank (Frontiers in Nuclear Medicine, 2022)
Prostate cancer (PCa) is one of the most common cancer types worldwide. 90% of men with late stage PCa will develop bone metastases. Since the expression level of PSMA (prostate-specific membrane antigen) in bone metastases can vary significantly, a compound is being searched for which accumulates in bone metastases independently of PSMA level. With DOTA L Lys(SA.Pam)-PSMA-617, we present a compound that, in addition to a PSMA inhibitor as a target vector, also contains a bisphosphonate that is established as a bone tracer and thus combines the advantages of PSMA targeting and bone targeting. This is a class of small molecules combining targeting of two different targets with the potential advantages for treatment of biologically heterogeneous bone metastasis from prostate cancer. The molecule can be labelled with lutetium-177 and used for the therapy of PCa-related bone metastases. DOTA-L-Lys(SA.Pam)-PSMA-617 was synthesized and radiolabelled in 1 M ammonium acetate buffer pH 5.5 at 95 °C. Different amounts of precursor were evaluated. Complex stability was evaluated in three different media. LogD7.4 value was evaluated via the determination of the equilibrium distribution in a PBS/n-octanol mixture. A hydroxyapatite binding assay was used to evaluate the potential binding to bone metastases. In vitro affinity was determined and Ki value was evaluated. To evaluate the binding potential in mice, ex vivo biodistribution studies were carried out in LNCaP tumor-bearing Balb/c mice. [177Lu]Lu-labelling of DOTA-L-Lys(SA.Pam)-PSMA-617 showed quantitative RCY within 10 minutes and high complex stability over 14 days. The lipophilicity of the labelled compound was similar to the lipophilicity of the reference compound [177Lu]Lu-PSMA-617 and showed an excellent and selective HAP binding of 98.2 ± 0.11%. With a Ki of 42.3 ± 7.7 nM PSMA binding affinity is lower in comparison to [177Lu]Lu PSMA-617. First ex vivo biodistribution studies with LNCaP tumor-bearing Balb/c mice showed a PSMA dependent tumor accumulation of 4.2 ± 0.7%ID/g and a femur accumulation of 3.4 ± 0.4%ID/g. [177Lu]Lu-DOTA-L-Lys(SA.Pam)-PSMA-617 is a promising compound for theranostic of PCa related bone metastases. Accumulation on the bone metastases via two mechanisms also enables the treatment of bone metastases that show little or no PSMA expression.